A SOCIOLINGUISTIC ANALYSIS OF APPELLATIONS IN OHIMINI LOCAL GOVERNMENT AREA OF BENUE STATE - LUCY OYIDU IKWU; THERESA D. IDOKO (International Studies Journal)
This study is a sociolinguistic analysis of appellations among the Idoma speaking people of Ohimini Local Government Area of Benue State. The objectives were to identify the appellations and analysis these appellations using Dell Hymes’s model of SPEAKING. This is a descriptive research and data was elicited through observation, and informal interviews from selected respondents. Also, the intuitive knowledge of the researchers and secondary sources provided additional data. The findings reveal that appellations do exist and are used when greeting among Idoma speakers of Ohimini LGA. These appellations are gender and clan specific, can be traced to the progenitors of a clan and can be used alone or in conjunction with statutory greetings. Furthermore, these appellations help to preserve and promote the culture, pass down history and traditions of the people, convey information about a person’s lineage as well as foster a sense of oneness and brotherhood. This study, therefore, has shed light on an aspect of the culture of the Idoma people of Ohimini LGA and added to the body of written works on the Idoma language.